Perencanaan Dan Pembuatan Rangka Wahana Multicopter Tipe Empat Baling-Baling (Quadcopter) - Vicry Darmawan; Kaspul Anuar; Musthafa Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Quadcopter is an unmanned flying vehicle whose lift force is produced by the rotation of the driving motor. One type of multicopter that is widely used to conduct aerial mapping missions is the quadcopter type. In this study the design of a quadcopter frame structure that was able to fly for more than 20 minutes with a MTOW quadcopter flying vehicle was 5 kg. The quadcopter used in this study is the hexacopter type X with a dimensions of the quadcopter frame of 790 mm were obtained based on the motor and propeller used. The MTOW of quadcopter is 563 gram.Quadcopter is made using carbon fiber composite material on the arm and middle plate, acrylic material on the clamp and polyacid material on the mounting. In the process of planning and making a carbon fiber composites, it is carried out using the hand lay-up and vacuum bagging method. So, that the results obtained with a wheelbase length of 787 mm and a diagonal of the middle plate of 200 mm, with MTOW is 679 gram. Keywords: Quadcopter, Frame, Carbonfiber, Hand Lay-up and Vacuum Bagging, MTOW